Faba Bean (Vicia faba L.) Nodulating Rhizobia in Panxi, China, Are Diverse at Species, Plant Growth Promoting Ability, and Symbiosis Related Gene Levels - Chen, Yuan X.; Zou, Lan; Penttinen, Petri; Chen, Qiang; Li, Qi Q.; Wang, Chang Q.; Xu, Kai W. (Frontiers in Microbiology, 2018)
We isolated 65 rhizobial strains from faba bean (Vicia faba L.) from Panxi, China, studied their plant growth promoting ability with nitrogen free hydroponics, genetic diversity with clustered analysis of combined ARDRA and IGS-RFLP, and phylogeny by sequence analyses of 16S rRNA gene, three housekeeping genes and symbiosis related genes. Eleven strains improved the plant shoot dry mass significantly comparing to that of not inoculated plants. According to the clustered analysis of combined ARDRA and IGS-RFLP the isolates were genetically diverse. Forty-one of 65 isolates represented Rhizobium anhuiense, and the others belonged to R. fabae, R. vallis, R. sophorae, Agrobacterium radiobacter and four species related to Rhizobium and Agrobacterium. The isolates carried four and five genotypes of nifH and nodC, respectively, in six different nifH-nodC combinations. When looking at the species-nifH-nodC combinations it is noteworthy that all but two of the six R. anhuiense isolates were different. Our results suggested that faba bean rhizobia in Panxi are diverse at species, plant growth promoting ability and symbiosis related gene levels.